La situación de las migraciones internacionales mixtas, un desafío constante para el derecho internacional de los refugiados y el derecho de asilo (2013)
This article lists the most significant historical events with respect to international migration in the twentieth century, which can be regarded as the century of mass migration and the uprooted. the goal is to reflect on the behavior that has maintained this phenomenon in the past, to define its current situation, and to understand the trends in migration so far during the twentyfirst century. the connections between immigration and asylum are identified, as are their differences. both these phenomena are closely related but must be treated differently.